IInterpretasi Dan Makna Kritik Sosial Dalam “Komik Strip Untuk Umum (Kostum)” Periode 1 Desember – 31 Desember 2017 - Salam, Babus; Prasetyo, Iwan Joko; Susilo, Daniel (Universitas Serang Raya, 2018)
Theres many ways can be done to appreciate the voices of messages and criticisms through creative ways, one of them through comics. One of the Indonesian comic artists who used comics as a medium of social criticism was Haryadhi through his